2018
DOI: 10.1002/hyp.13273
|View full text |Cite
|
Sign up to set email alerts
|

An hourly‐scale scenario‐neutral flood risk assessment in a mesoscale catchment under climate change

Abstract: Reliable assessments of flood risks are essential to formulate robust adaptation policies to climate change. Although the scenario-neutral flood assessments have reduced the dependency on uncertain climate predictions, coarse temporal resolutions of rainfall-runoff modelling adopted for the stress tests may introduce appreciable bias to flood risks driven by climatic stresses. To refine the temporal scale of flow estimates, this study proposes to incorporate a multiplicative random cascade (MRC) scheme and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…A scenario hypothesis is used to simulate the hydrological response of flooding under a certain climate scenario in the future and then analyze the flood risk [31][32][33]. The hydrological response to climate change is the basis of the study on the influence of climate change on flood risk.…”
Section: Scenario Hypothesismentioning
confidence: 99%
“…A scenario hypothesis is used to simulate the hydrological response of flooding under a certain climate scenario in the future and then analyze the flood risk [31][32][33]. The hydrological response to climate change is the basis of the study on the influence of climate change on flood risk.…”
Section: Scenario Hypothesismentioning
confidence: 99%
“…To overcome the uncertainties and problems associated with model cascades, alternative approaches are currently being developed (Guo et al, 2017;Knighton et al, 2017;Kim et al, 2018;Broderick et al, 2019;Keller et al, 2019a;Keller et al, 2019b). In studies investigating the impacts of climate change on hydrology, a scenario-neutral approach has been used to analyze the sensitivity of river flows to changes in temperature and precipitation, where the observed rainfall and temperature data are modified by stepwise increases or decreases in the value of associated parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Among the decision-centric frameworks, the assessments based on the response functions of system performance have provided convenience in defining decision thresholds at which adaptation actions are required (e.g., Kim et al, 2018;Steinschneider et al, 2015a;Turner et al, 2014;Whateley et al, 2014;Brown et al, 2012;Prudhomme et al, 2010). They developed the relationships between system performances and climatic stressors (hereafter referred to as the response surfaces) via stress tests.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, uncertainty of the response surfaces cannot be neglected due to assumptions and simplifications associated with the stress tests. Kim et al (2018), for instance, showed how climate change risks could be underestimated if a modeling scale was inappropriately chosen. Kay et al (2014) emphasized the importance of uncertainty allowances being used alongside the response surfaces.…”
Section: Introductionmentioning
confidence: 99%